PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK SISWA DI SMP ALAM LAMPUNG - Rahmatullah, Syabani; Ahmad Luviadi; M Sholihin; Arizal Eka Putra (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2026)
Abstract. This study examines the role of Islamic Religious Education (PAI) teachers in developing students' morals at SMP Alam Lampung. In the context of environmental education and Islamic values, PAI teachers act as educators, mentors, and role models who consistently instill Islamic moral values ​​through habituation, role modeling, and ongoing supervision. This study used qualitative methods with data collection techniques including interviews, observations, and archival documentation of moral development as the primary sources. The results indicate that PAI teachers play a significant role in shaping students' character by integrating the values ​​of honesty, patience, trustworthiness, and humility into daily activities and nature-based learning. Furthermore, teacher role models in attitudes and behavior are key factors in the success of developing students' morals. Obstacles encountered include unstable student character and external environmental influences, which are addressed through motivational approaches, supervision, and communication with parents. In conclusion, moral development through the role of PAI teachers at SMP Alam Lampung is effective in shaping students' Islamic character, with contextual learning that can be further developed to improve student discipline and morals.